Teaching Methods in Science Subjects Promoting Sustainability - Eila Jeronen (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
In this book, conventional and new methods through which sustainability can be promoted in mathematics and science subjects are described and discussed. The aim of the book is to support teachers and teacher educators in their work, and to create a multi-sided view on sustainability, and on education for sustainable development. Curriculums and teaching approaches for the implementation of sustainability in schools and universities, especially in teacher education, are discussed. The pedagocical studies presented give useful examples of how sustainability can be included in mathematics, physics and biology education. The described teaching methods are discussed also in relation to students' competence and learning outcomes. In addition, valuable ideas are presented for the development of curriculums and teaching practices in higher education and schools. The book is suited for all teachers and researchers who are interested in sustainability and sustainable development, and want to develop their teaching in higher education and schools.